Characterization of ralstonia solanacearum (Smith) Yabuuchi et al. causing bacterial wilt in ginger using molecular marker - Sambasivam P K (Department of Plant Pathology, College of Horticulture, 2003)
In Kerala, bacterial wilt caused by Ralstonia solanacearum is one of the major constraints in ginger cultivation. Earlier, the pathogen was characterized based on cultural, morphological and biochemical tests. Since these methods are time consuming and involve repeated subculturing and tedious biochemical tests, an attempt was made to characterize the pathogen at molecular level using plasmid profile and RAPD technique. Wilted plant samples were collected from ginger growing tracts of Palakkad, Eranukulam and Wynad districts. The pathogen was isolated on TZC medium, it produced creamy white pink centred fluidal colonies. Stock cultures prepared by suspending single colonies in sterile water were maintained at 4 QC. Pathogenicity of the isolates was established using pseudostem inoculation method. Tomato and brinjal were found to be collateral hosts of the pathogen. Based on hypersensitivity reaction on capsicum the isolates were identified as race 3. This was further confirmed by RAPD assay. The isolates were found to. be Gram negative and showed positive reaction for solubility. in KOH, nitrate reduction, production of catalase and oxidase enzyme, fermentation of glucose. All the isolates utilized lactose, maltose, cellobiose, manitol, sorbitol but not dulcitol and hence, were grouped as biovar III A. Plasmid profile developed for the isolates showed presence of two bands of . . approximately 21 kb size .. Plasmids when transformed to E. coli DH 5a cells, conferred resistance to ampicillin and rifampicin, indicating that the genes encoding resistance to these antibiotics were located on the plasmid.